PENGARUH MODEL PEMBELAJARAN LEARNING TOURNAMENT TEHADAP HASIL BELAJAR PPKn SISWA KELAS VII SMPN 3 XIII KOTO KAMPAR - Asriatul Rahma; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low student learning outcomes of PPKn at SMPN 3 XIII Koto kampar. The formulation of the problem in this study is "is there any influence of the use of Learning Tournament learning models on learning outcomes whether students in class VII SMPN 3 XIII Koto Kampar?". This study aims to determine the effect of the use of Learning Tournament learning models in improving the learning outcomes of PPKn grade VII SMPN 3 XIII Koto Kampar. This research was conducted at SMPN 3 XIII Koto Kampar in November 2018.  This research is a quantitative descriptive research that was experimental. The population in this study were students of class VII SMPN 3 XIII Koto Kampar, The sample in this study was taken based on "Random Sampling" technique. where the classes taken into the sample were students of class VII.C (experimental class) who were given a Learning Tournament learning model, and class VII.B (control class) were students who were given conventional methods. Then the data were analyzed using homogeneity test and "t" test. The subject matter that is applied  is the "Formulation and retatification of Indonesian in 1945". Based on the results of the study indicate that there is an influence of learning outcomes between students who use Learning Tournament models and conventional methods in SMPN 3 XIII Koto Kampar. this can be seen from the results ( 14to=4,29"> > 14ttable=2,01290"> ). Thus there is an effect of the use of Learning Tournament learning models on student learning outcomes VII. The magnitude of the effect after being calculated with a gain test shows the Learning Tournament learning model gives an effect on learning outcomes of 0,45 in the medium category. Where there was an increase in the average learning outcomes of the experimental class to 74,16 and the average increase in the learning outcomes of the control class was 59,79. Key Words : Learning Tournament, Learning Outcomes